A ―CORAGEM DE SER‖ CLARICE: a centralidade da existência humana como expressão da religião na obra de Clarice Lispector estudada a partir da teologia da cultura de Paul Tillich - Tada, Elton Vinicius Sadao (2015)
This essay studies the centrality of the human existence as the expression of religion in Clarice Lispectors work. The notion of religion used derives from the concept of theology of culture proposed by the german-american philosopher and theologist Paul Tillich and its consequences, as the concept of the courage to be, faith, revelation, non-being and being-itself. The study is based on short stories and novels published by Clarice Lispector, covering several thematic as body, sexuality, gender, poverty, identity, belonging and otherness. The thesis defended is that exist religious preoccupations at Clarice Lispectors literature, considering Tillichs notion. This problematic is expressed both in short stories as in novels by the thematics as well as the textual structure. Clarice Lispectors work exhibit a huge questioning about existence considering the origin, the ending, the purpose and meaning of existence, approaching the religious foundation of cultural expression. This religious foundation appears as a constant, a continuous line from which can be understood in a deeper way both the sense of unity of the complete work of the Brazilian writer as well as the particularities of the narratives according to different perspectives. Our hypothesis is that there is, in Clarices literature, a moment when the characters experience an event that makes them face their existential situation in a new or different way. These events are basically the shock with the non-being, the encounter with the nothingness that is in the basis of the literary construction of the characters.